THE IMPLEMENTATION OF LINE WEBTOON TO ENHANCE STUDENTS’ READING COMPREHENSION - Retnoningrum, Jasmine Aryanti; Usman, Sriati; Dewi, Anjar Kusuma; Aminah, Aminah (e-Journal of ELTS (English Language Teaching Society), 2024)
This research aims to determine whether or not the implementation of Line Webtoon can enhance the reading comprehension of the eight grade students of SMP Negeri 4 Palu. The population of this research is the eighth-grade students of SMP Negeri 4 Palu. The sample was VIII A as the experimental class and VIII B as the control class. The research applied the quantitative method. The instrument of the data collection was pre-test and post-test. Those data were analyzed statistically. The pre-test was at a low level, and the post-test was at a high level. The pre-test was low because the students had difficulties in reading comprehension. However, the post-test that at a high level because of the media can enhance students’ reading comprehension. The results of the data analysis show that the t-counted was greater than the t-table. In conclusion, using line webtoon can enhance students’ reading comprehension.